2013
DOI: 10.1016/j.vetimm.2012.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial epithelial cells are potent producers of tracheal antimicrobial peptide and serum amyloid A3 gene expression in response to E. coli stimulation

Abstract: Endometrial epithelial cells play a critical role in mediating inflammatory mechanisms key to bacterial clearance and tissue re-modelling postpartum. This study characterised innate immune gene expression by bovine endometrial epithelial cells from three animals in response to Escherichia coli, a common cause of bovine uterine disease. Expression of key innate immune genes, encoding Toll-like receptor 4 (TLR4), the transcription factor NFkB1, the chemokine interleukin 8 (IL8), inflammatory cytokines (interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…The animals had no evidence of genital disease based on visual inspection and the uteruses were obtained in accordance with protocols approved by the local Institutional Animal Care and Use Committee. Primary bEECs were isolated from the endometrium as described previously (Chapwanya et al, 2013). In brief, the endometrium was sliced into small pieces measuring about 3-5 mm 3 and digested with sterile filtered digestive solution (50 mg trypsin, 50 mg collagenase II, 100 mg BSA, and 10 mg DNase I) for 1 h in a gently agitating water bath at 37 °C.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals had no evidence of genital disease based on visual inspection and the uteruses were obtained in accordance with protocols approved by the local Institutional Animal Care and Use Committee. Primary bEECs were isolated from the endometrium as described previously (Chapwanya et al, 2013). In brief, the endometrium was sliced into small pieces measuring about 3-5 mm 3 and digested with sterile filtered digestive solution (50 mg trypsin, 50 mg collagenase II, 100 mg BSA, and 10 mg DNase I) for 1 h in a gently agitating water bath at 37 °C.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Endometrial epithelial cells line the uterine mucosal surface, forming a physical barrier to protect the host from pathogen invasion (Wira et al, 2005). Endometrial epithelial cells in the bovine uterus were found to recognize and respond to pathogens via surface receptors such as TLRs (Chapwanya et al, 2013;Turner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SAA3 is produced primarily extrahepatically but also at low levels by the liver (19). SAA3 production has been demonstrated in mouse macrophages (20), bovine endometrial epithelium (21), and in a wide‐range of extrahepatic tissues across species (22). However, SAA3 has not been reported as a cause of amyloidosis.…”
mentioning
confidence: 99%
“…These cells express PRRs such as TLRs [18] and are able to mount an innate immune response to bacteria [19] or bacterial ligands such as LPS [20] [21].…”
Section: Introductionmentioning
confidence: 99%